Islam hétérodoxe et christianisme en Grèce - Isabelle Dépret (Cahiers Balkaniques)
In South-Eastern Europe, Alevism and Bektashism constitute two tightly connected religious movements whose roots go down to the Ottoman history of this area. This branch of Islam belongs to Sufi traditions, integrates elements of Shiism as well as various influences, among which shamanism. In Greece, alevism-bektashism still exists in Western Thrace, in a Turkish-Bulgarian-Greek cultural environment. A few alevi communities live especially in mountainous villages, in the North of the Xanthi and Evros administrative circonscriptions. Cultivating a community memory, the Alevis of Western Thrace seem to be torn today between withdrawal, assimilation to sunnism, secularization and revitalization of cross-border networks. As a minority within the “Muslim minority” of Thrace, this religious group is little known in Greece. Greek social sciences scholars who followed, in this respect, the readings of prominent 19th-20th centuries European Orientalists have often studied this group under the prism of christianism. Long ignored or despised as a specific community, the Western Thrace bektashis are also directly in contact with Turkish nationalism – promoted by local or international protagonists – and with newly revitalized Alevi networks. A school clash in an alevi – and predominantly Pomak – village enables us to examine the interplay of religious identity and otherness, national narratives and political strategies. This case study – in which local, national and foreign policy factors are intertwined – reminds us that Islam has remained a highly sensitive issue in Greece.